Effectiveness of Lentinus edodes Mushroom Extract on Eradication of Enterococcus faecalis Biofilm - Anggiarini, Putri Lestari; Amin, Meiny F; Gunawan, Juanita A; Widyarman, Armelia Sari (UI Scholars Hub, 2020)
Sodium hypochlorite is a commonly used irrigation solution in endodontic procedures, but it irritates tissues and has toxic effects. Lentinus edodes is a mushroom that has antibacterial properties. Enterococcus faecalis is an anaerobic bacterium that can cause root canal treatment failure. Objective: This study aimed to determine the effect of L. edodes extract on the eradication of E. faecalis biofilms. Methods: Phytochemical tests of L. edodes were performed to analyze alkaloids, steroids, triterpenoids, phenolics, tannins, flavonoids, and glycosides from this extract qualitatively. E. faecalis ATCC 29212 was cultured in brain heart infusion broth for 24 h at 37°C in an anaerobic atmosphere. Biofilm assay was performed to analyze the eradication of E. faecalis biofilm after treatment with L. edodes extract. The application times were 5, 15, and 30, and 10%, 20%, 40%, and 80% concentrations were used. Distilled water was used as a negative control, and NaOCl was used as a positive control. Data were statistically analyzed via one-way analysis of variance, where p < 0.05 was set as the level of significance. Results: L. edodes mushroom extract was effective in eradicating E. faecalis biofilms in all concentrations and incubation times compared with the control (p < 0.05). Significant differences were found between the application times of 5 and 15 min compared with 30 min (p < 0.05). The most effective concentration in eradicating E faecalis biofilms was 40% with an application time of 30 min. Conclusion: L. edodes mushroom extract proves its antibiofilm activity against E. faecalis biofilm. Further study is necessary to determine which substances are have the most influence on the effectiveness of L. edodes extract in eradicating E. faecalis biofilm in vivo.